The Effectiveness of Plasma Convalescent in Pregnant Women with COVID-19 At Unggul Karsa Medika Hospital: A Case Series - Aloysius Suryawan; Theresia Monica Rahardjo; Rizna Tyrani Rumanti; Angel Yustina Ngongo; Difati Cesar Marselino; Indry Andy Ginting; Johanna; Liana Alvitri; Sharone Amabel; Tiara Margaretha Tabolong; Trengginas Aji Suroso; Yosua Kristian Setia Budi (Rumah Sakit Unggul Karsa Medika, 2023)
At the beginning of 2020, a pandemic caused by a novel coronavirus began to have devastating effects worldwide. The etiological agent was Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) and the disease named coronavirus disease or COVID-19. Nearly 109 million people have been infected by the virus and more than 2.4 million people have died. An intense debatehas started on therapeutic possibilities for COVID-19 in pregnancy. The management of the disease is essentially driven by the symptoms. Asymptomatic or pauci-symptomatic women do not require inpatient care or medications, but simply need monitoring of respiratory function for up to two weeks for evidence of deterioration. Convalescent plasma from individuals who have recovered from COVID-19, a blood component that is not contraindicated in pregnant women and has been transfused safely for at least 30 years, deserves special consideration.